Self-Control and Religiosity of Students on Deviant Online Behavior in the Perspective of Islamic Education - Nazwa Salsabilla; Munawarah Munawarah; Saifa Ananda Putri; Noviani Hidayah; Surawan Surawan (unprimdn.ac.id, 2026)
The development of digital technology provides students with ease in accessing information and interacting through social media. However, technology use that is not accompanied by self-control and the internalization of religious values may lead to deviant online behavior. This study aims to analyze the relationship between self-control and religiosity and deviant online behavior among students from the perspective of Islamic education. This research employed a quantitative approach with a correlational design. The participants were 53 students of SMAN 1 Tewah selected using purposive sampling based on the criteria of actively using social media, being 16-17 years old, and being willing to participate. Data were collected using a closed-ended Likert-scale questionnaire distributed through Google Forms. The instrument was examined through validity testing and Cronbach's Alpha reliability testing, while the data were analyzed using the Kolmogorov-Smirnov normality test and Spearman's rho correlation test because not all variables were normally distributed. The validity test showed that 13 of 15 items were valid, while the reliability test showed Cronbach's Alpha values of 0.657 for self-control, 0.685 for religiosity, and 0.780 for deviant online behavior. The correlation test showed a significant relationship among self-control, religiosity, and deviant online behavior (Sig. 0.000 < 0.05). The correlation coefficients indicated strong relationships between self-control and religiosity (r = 0.603), self-control and deviant online behavior (r = 0.648), and religiosity and deviant online behavior (r = 0.714). These findings indicate that self-control and religiosity are internal factors related to students' behavior in digital spaces. Therefore, strengthening religious values and developing self-control through Islamic Religious Education should be emphasized to foster wiser and more responsible digital behavior.